From mass to networked communication: communicational models and the informational society - Cardoso, G. (International Journal of Communication, 2008)
Focusing on the analysis of the more widespread media in our societies — television — this paper addresses what is considered to be the basic characteristic of the current media system, that is, the networking between interpersonal and mass media. During the last 15 years, we have witnessed a vast change in the media landscape. A change, not only due to technological innovation in mediation devices themselves, but also in the ways users have chosen to socially appropriate them, and consequently, how they have built new mediation processes. Change in mediation has been, during the last few years, the focus of the analysis of many scholars in the social sciences. We have gone beyond a communication model based in mass communication and into a communication model based in networked communication. This paper addresses what it is suggested to be the networking communicational model of informational societies. A communicational model shaped by three main features: 1) Communicational globalization processes; 2) Networking of mass and interpersonal media and consequently, networked mediation; and 3) Different degrees of interactivity usage. The second part of this paper deals with what is argued to be the new communicational paradigms giving rise to a new media system: 1) Rhetoric mainly built around moving image; 2) New dynamics of accessibility of information; 3) Users as innovators; and 4) Innovation in news and entertainment